Antiproliferative and apoptotic effect of herbal formulation containing black and green tea extract against HCT-116 human colon cancer cells - S.Jeswin Immanuel; Parameswari R P; Lakshmi Thangavelu (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Due to their safety, greater tolerance, and economics, phytochemical-based dietary interventions have drawn attention as a preventive and therapeutic method against most cancers. The purpose of this study was to investigate the antiproliferative and apoptotic effect of black and green tea formulation.Materials and Methods: Aqueous extracts of black and tea were prepared. The formulation was prepared by mixing 1:1 part of individual aqueous extracts of black and tea. The prepared formulation was evaluated for in vitro cytotoxicity using HCT-116 colon cancer cells. Morphological changes were observed and the apoptotic effect of the formulation was also assessed.Results: The results showed that the formulation was able to inhibit the growth of colon cancer cells effectively at all the tested concentrations between the range of 5-50μg/ml. A dose-dependent decrease in the viability of cells was observed. IC50 was calculated by linear regression analysis. Based on the IC50, efficacy concentration of 45μg/ml was chosen for morphology and dual staining assays. Morphological changes were observed after treating the cells at a single concentration of 45μg/ml. The treated cells demonstrated loosely adhered boundaries with spherical morphology indicating the onset of the cell death following the black and green tea formulation treatment. To further confirm the antiproliferative effect, the formulation treated cells were stained with ethidium bromide/acridine orange and assessed for apoptotic effect. The images showed greenish yellow fluorescent cells in addition to few green fluorescent cells when compared to untreated cells that appeared only green in fluorescence.Conclusion: Hence from the results of the present study it may be concluded that the black and green tea formulation were found to show significant antiproliferative and apoptotic effect in HCT 116 colon cancer cells.